Cost Accounting - Das, Prabir (Shah Alam, Selangor: Oxford Fajar SB, 2013)
Cost Accounting Fifth Edition is a book intended for a wide range of users and it covers both theory and techniques of cost accounting.
Includes index
Keywords: Accounting; Cost Accounting